Anti-pollution modified hollow fiber membrane as well as preparation method and application thereof

By using anti -pollution modified materials and processes in the hollow fibrous membrane, the problem of being vulnerable to pollution during use in the process of using the membrane has been solved, long -acting antibacterial and anti -pollution properties are achieved.

CN119345913APending Publication Date: 2025-01-24深圳市水务规划设计院股份有限公司

Patent Information

Application Number
CN202410193507.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing hollow fiber membranes are susceptible to physical and biological contamination during use, resulting in reduced treatment efficiency, shortened life and increased maintenance costs, and it is difficult for modified materials to maintain a long-term anti-pollution effect.

Method used

Adopt a method of anti -pollution modified hollow fiber membrane preparation method. By mixing polytin fluoride, modified materials and additives with organic solvents, it has been drifted and sprayed into a film. Antibacterial and anti -pollution membrane.

Benefits of technology

The long-term antibacterial and anti-pollution properties of the hollow fiber membrane are achieved, reducing membrane pollution, extending the service life of the membrane, and reducing maintenance and replacement costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345913A_ABST
    Figure CN119345913A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-pollution modified hollow fiber membrane and a preparation method and application thereof.The anti-pollution modified hollow fiber membrane can be tightly combined with a zwitterionic polymer material modified nano-antibacterial material, and is prepared from, by weight, 8-30% of polyvinylidene fluoride (PVDF) / polysulfone / polyethersulfone, 0.1-15% of a modified material, 0.1-10% of an antioxidant and the balance water. According to the present invention, the prepared hollow fiber membrane has characteristics of excellent pollution resistance, no filament breaking, and application in wastewater treatment, pollution control, water resource comprehensive utilization, food processing, medicine purification, and other aspects, and the prepared hollow fiber membrane has characteristics of excellent pollution resistance, no filament breaking, and can be used in the fields of wastewater treatment, pollution control, water resource comprehensive utilization, food processing, medicine purification, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of new materials, energy conservation and environmental protection, sewage treatment, and in particular to a hollow fiber membrane and a preparation method thereof. Background Art

[0002] Membrane technology can be applied to water treatment, food processing and pharmaceutical purification. Compared with traditional water treatment technology, membrane technology has many advantages in water treatment, including good effluent quality, high treatment efficiency and no secondary pollution. However, membrane fouling has always been a key factor affecting the efficiency of membrane application. First of all, membrane fouling will significantly affect the efficiency of the membrane treatment process. Pollutants can block the pores or surface of the membrane, resulting in increased flow resistance and affecting the membrane flux. This means that the membrane treatment system requires higher pressure or more frequent cleaning to maintain normal operation. This not only increases energy consumption, but also increases operating costs. Secondly, membrane fouling will also affect the life and stability of the membrane. Pollutants may cause damage or degradation of the membrane material, shorten the service life of the membrane, and bring higher replacement and maintenance costs.

[0003] In the operation of water plants, microfiltration and ultrafiltration hollow fiber membranes are widely used. However, during use, physical and biological pollution is relatively serious. Therefore, it is particularly important to develop a hollow fiber membrane that can effectively resist bacteria and pollution. The conventional modification method is to add modified materials to the membrane material, which can play an effective anti-pollution role to a certain extent and time. However, as the operating time increases, the modified materials are often easily separated from the membrane structure and infiltrated into the water, and thus cannot continue to play an anti-pollution role. On the other hand, most modified materials can only play a relatively significant effect in physical anti-pollution, but the effect on biological pollution is not obvious. Therefore, introducing stable and effective antibacterial and anti-fouling modified materials into the membrane structure will play an effective role in combating physical and biological pollution. Summary of the invention

[0004] The present invention aims to provide a method for preparing a hollow fiber membrane with long-lasting antibacterial and anti-pollution properties.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing an anti-pollution modified hollow fiber membrane, comprising the following steps:

[0006] S1: 8% to 30% of polyvinylidene fluoride PVDF or polysulfone or polyethersulfone, 0.1% to 15% of modified material, 0.1% to 30% of additive and 25% to 88.9% of organic solvent are mixed and injected into a reaction kettle, and stirred and dissolved at 60 to 110° C. for 6 to 24 hours, wherein the weight average molecular weight of the polyvinylidene fluoride is 200,000 to 800,000.

[0007] S2: Dissolve the solution in S1 and transfer it to a degassing tank, and let it stand in the degassing tank at 30-80°C for 2-10 hours to obtain a homogeneous casting liquid. Squeeze the degassed casting liquid from the degassing tank into a metering pump at 0.5-3 bar and then inject it into a spinneret. The temperature of the spinneret is controlled at 44-70°C, and the spinneret temperature is lower than the coagulation bath temperature.

[0008] Then, the membrane is immersed in a coagulation bath tank filled with tap water at 25-83°C and a rinsing tank at 35-75°C in turn for phase transformation into a membrane. The membrane is immersed in the coagulation bath tank and the rinsing tank for 1-600 seconds respectively. The membrane fibers after membrane formation are collected through a winding wheel and immersed in pure water for 8-48 hours. After being immersed in a post-treatment solution for 24 hours, an anti-pollution modified hollow fiber membrane is obtained.

[0009] Preferably, after the deaerated casting solution is injected into the spinneret and before it is immersed in the coagulation bath, the following steps are added to finally obtain the lining-enhanced anti-pollution modified hollow fiber membrane: the treated lining tube is passed through the center of the spinneret, and under the joint action of the braided tube and the metering pump, the deaerated casting solution and the fiber braid are extruded from the spinneret together, and the deaerated casting solution is evenly coated on the outer surface of the fiber braided tube. The lining material uses ethylene terephthalate (PET).

[0010] Preferably, the modified material in S2 is one or more of titanium dioxide, other metals or metal oxides, zwitterionic polymer modified antibacterial titanium dioxide, polyurethane, sulfonated polysulfone, polymethyl methacrylate, amino polysulfone, polyvinyl alcohol and chitosan. The size of the modified antibacterial titanium dioxide or the unmodified titanium dioxide is 20 to 120 nm. When the organic solvents are mixed in several ways, they can be randomly proportioned in any proportion.

[0011] Preferably, the additives in S2 include one or more of plasticizer, dibutyl phthalate, silicone polymer, glycerol, diethyl phthalate, polysorbate-80, saturated fatty acids, sorbitan fatty acid esters, saturated fatty acid salts, sodium dodecylbenzene sulfonate, sodium glycocholate, sodium linear alkylbenzene sulfonate, sorbitan oleate, Tween 20, Span 85, polyethylene glycol, glutaraldehyde, epichlorohydrin and polyvinyl pyrrolidone. When several additives are mixed, they can be randomly proportioned in any proportion.

[0012] Preferably, the organic solvent in S2 is one or more of propylene glycol, glacial acetic acid, phytic acid, isopropanol, n-hexane, n-heptane, n-hexanol, acetone, methanol, triethyl phosphate, N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide and ethyl acetate. When several organic solvents are mixed, they can be randomly mixed in any proportion.

[0013] Preferably, the preparation method of zwitterionic polymer material modified antibacterial titanium dioxide is as follows:

[0014] 1) Add 20-50 parts of tetraisopropyl titanate to 40-110 parts of isopropanol, and then drop the mixture into 800-2000 parts of deionized water and nitric acid, or deionized water and hydrochloric acid solution, and stir vigorously while fixing the pH value at 1-4. After 24 hours, a transparent TiO2 sol is obtained. Among them, 20 parts, 30 parts, 40 parts or 50 parts of tetraisopropyl titanate can be selected; 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts or 110 parts of isopropanol can be selected; 800 parts, 900 parts, 1000 parts, 1200 parts, 1500 parts, 1800 parts or 2000 parts of the solution composed of deionized water and nitric acid or the solution composed of deionized water and hydrochloric acid can be selected; and the pH value can be fixed at 1, 2, 3 or 4.

[0015] To make the Ag content in the TiO2 nanoparticles 3-7 wt.%, add the required amount of AgNO3 0.8-1.1 parts of solution to the aforementioned TiO2 sol and stir for 10-40 minutes to allow Ag to + ions adsorbed onto the TiO2 surface; then, Ag was reduced by dropwise addition of 0.2 parts of ascorbic acid (200-400 mL). + , until a color change from colorless to brown was observed to obtain colloidal TiO2-Ag nanoparticles.

[0016] In order to increase the specific surface area of ​​the final powder, the gel was dehydrated using the azeotropic dehydration method of benzene. In this process, the colloidal TiO2-Ag nanoparticles were heated to 110°C to obtain a viscous gel, which was then transferred to a double-necked flask containing benzene. The flask was circulated with water and the temperature was raised to 70-100°C while stirring continuously. When the column was filled with a water-benzene mixture, water was extracted from the outlet. After 24 hours, the yellow solution in the flask was filtered, and finally the prepared powder was calcined in air at 300°C and 500°C for 2 hours to obtain antibacterial modified titanium dioxide.

[0017] 2) Dispersing 3 to 20 parts of the dried antibacterial modified titanium dioxide in step 1) in 50 to 500 parts of toluene and stirring for 30 minutes, wherein the antibacterial modified titanium dioxide can be selected from 3 parts, 5 parts, 8 parts, 10 parts, 15 parts or 20 parts; and the toluene can be selected from 50 parts, 70 parts, 80 parts, 100 parts, 150 parts, 200 parts, 250 parts, 300 parts, 400 parts, 450 parts or 500 parts. Then, 20 to 100 parts of 3-aminopropyltriethoxysilane are added, and the reaction mixture is stirred, wherein 20 parts, 50 parts, 80 parts or 100 parts of 3-aminopropyltriethoxysilane can be selected, and refluxed in a nitrogen atmosphere at 60 to 150° C. for 8 to 20 hours. After the reaction is completed, toluene and acetone are used, centrifuged (3000 to 6000 rpm, 3 to 7 minutes), and vacuum dried at 40 to 70° C. for 16 to 30 hours to obtain amino-modified antibacterial titanium dioxide;

[0018] 3) Dispersing 1 to 15 parts of the amino-modified antibacterial titanium dioxide in step 2) in 20 to 150 parts of toluene and 2 to 9 parts of triethylamine, wherein the amino-modified antibacterial titanium dioxide can be selected from 1 part, 3 parts, 5 parts, 8 parts, 10 parts, 12 parts or 15 parts; toluene can be selected from 20 parts, 40 parts, 60 parts, 80 parts, 100 parts, 120 parts or 150 parts; triethylamine can be selected from 2 parts, 4 parts, 5 parts, 8 parts or 9 parts; stirring at 0°C, adding 3 to 6 parts of 2-bromopropyl solution, wherein the 2-bromopropyl solution can be selected from 3 parts, 5 parts or 6 parts, and then dropping the bromide and 15 to 25 parts of toluene within 1 hour, wherein the toluene can be selected from 15 parts, 18 parts, 20 parts or 25 parts. The mixture was stirred at 0°C for 2 to 5 hours and finally stirred at room temperature overnight. At the end of the reaction, the product was washed with a water / acetone mixture (1 / 1, v / v), centrifuged (3000 to 7000 rpm, 3 to 8 min), and vacuum dried at 60°C for 18 to 30 hours to obtain bromine-modified antibacterial titanium dioxide.

[0019] 4) Disperse 1 to 10 parts of bromine-modified antibacterial titanium dioxide in step 3) in 10 to 200 parts of methanol, wherein bromine-modified antibacterial titanium dioxide can be selected as 1 part, 3 parts, 5 parts, 8 parts or 10 parts, and methanol can be selected as 10 parts, 30 parts, 50 parts, 80 parts, 100 parts, 120 parts, 120 parts, 180 parts or 200 parts. Stir the mixture for 10 to 40 minutes, add 0.5 to 4 parts of pentamethyldiethylenetriamine and 0.1 to 5 parts of CuBr / 0.1 to 5 parts of CuBr2 into a flask purged with nitrogen, wherein the amount of methyldiethylenetriamine added can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts; CuBr or CuBr2 can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 5 parts. Then, 1 to 15 parts of sulfobetaine methacrylate (SBMA) are added to the flask, and SBMA can be selected as 1 part, 3 parts, 5 parts, 8 parts, 10 parts, 12 parts or 15 parts, and the reaction is carried out at 50 to 75° C. for 8 to 15 hours through an atomic free radical reaction. Finally, the reaction mixture is washed with methanol and acetone, centrifuged (2000 to 6000 rpm, 2 to 8 minutes), and vacuum dried at 60° C. for 24 hours to obtain zwitterionic polymer material modified antibacterial titanium dioxide through an atom transfer free radical polymerization reaction.

[0020] The invention discloses an application of a hollow fiber membrane. The hollow fiber membrane can be applied to wastewater treatment, pollution prevention and control, comprehensive utilization of water resources, food processing and pharmaceutical purification.

[0021] Compared with the prior art, the present invention has at least the following advantages:

[0022] 1. The first aspect of the present invention provides a method for preparing silver-doped titanium dioxide. On the other hand, an organic functional group is introduced on the surface of the modified titanium dioxide by atomic radical transfer technology, and a zwitterionic polymer modified antibacterial nanomaterial with strong polymer binding is prepared by metal ion embedding and polymer grafting. A uniform modified membrane solution is prepared, and then a hollow fiber membrane spinning machine is used to draw the membrane, and the membrane is evenly dispersed in the membrane structure, so that the antibacterial and anti-pollution properties of the membrane are achieved, and the nanomaterial and the membrane material are tightly combined without leakage. This technology is the first to modify the antibacterial nanomaterial by atomic radical transfer technology and evenly embed it into the hollow fiber membrane structure.

[0023] 2. The hollow fiber membrane can be tightly combined with the nano-antibacterial material without leakage. Due to the chemical and physical properties of the material, water can be quickly dispersed in the pores and on the surface, reducing the resistance to water passage. At the same time, due to the special properties of silver-doped titanium dioxide, an antibacterial layer and a water film layer can be formed on the membrane surface, thereby playing an effective physical anti-fouling and biological anti-fouling role. At the same time, it has photocatalytic properties. To a certain extent, the overall filtration performance of the membrane can be improved after the nanomaterial is modified. At the same time, the nanomaterial does not leak while having antibacterial and anti-fouling effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The following are photos (a1) of the modified antibacterial titanium dioxide powder prepared in Example 1 of the present invention and photos (a2) of the modified antibacterial titanium dioxide hollow fiber membrane prepared in Example 4.

[0025] Figure 2 1 and 10. The cross-sectional view of the membrane in Example 5 of the present invention, (a1) is an electron microscope image magnified 900 times, and (a2) is an electron microscope image magnified 10k times.

[0026] Figure 3 This is a graph showing membrane flux changing with pressure in Example 5 of the present invention.

[0027] Figure 4 This is a diagram of membrane pollution test of the modified antibacterial titanium dioxide hollow fiber membrane in Example 4 of the present invention.

[0028] Figure 5 This is a diagram of the iron block for hanging the hollow fiber membrane in Example 6 of the present invention. DETAILED DESCRIPTION

[0029] The present invention is described in further detail below.

[0030] A hollow fiber membrane contains titanium dioxide or modified antibacterial titanium dioxide. The titanium dioxide has strong hydrophilicity and can form a water film to isolate pollutants during the filtration process. While ensuring a high flux and removal rate of the hollow fiber membrane, it also has excellent anti-pollution performance.

[0031] Examples 1-3 are examples of the preparation method of zwitterionic polymer material modified antibacterial titanium dioxide.

[0032] Example 1: A method for preparing zwitterionic polymer material modified antibacterial titanium dioxide, comprising the following steps:

[0033] 1) comprising preparing a 300 mM TiO2 sol by adding 20 mL of tetraisopropyl titanate to 40 mL of isopropanol, and dropping the mixture into 800 mL of deionized water and nitric acid or into 800 mL of deionized water and hydrochloric acid solution, while vigorously stirring and fixing the pH at 1. After 24 hours, a transparent TiO2 sol is obtained.

[0034] In order to achieve an Ag content of 3-7 wt.% in the TiO2 nanoparticles, the required amount of AgNO3 0.8 M solution was added to the existing TiO2 sol and stirred for about 10 minutes to allow the Ag to + ions adsorbed onto the TiO2 surface. Then, Ag was reduced by dropwise addition of 200 mL of ascorbic acid 0.2 M + , until a color change from colorless to brown is observed.

[0035] In order to increase the specific surface area of ​​the final powder, the gel was dehydrated using the azeotropic dehydration method with benzene. During this process, the colloidal TiO2-Ag nanoparticles were heated to 110°C to obtain a viscous gel. It was then transferred to a double-necked flask containing benzene. The flask was circulated with water and the temperature was raised to 70°C while stirring continuously. When the column was filled with a water-benzene mixture, water was extracted from the outlet. After 24 hours, the yellow solution in the flask was filtered, and finally the prepared powder was calcined in air at 300°C and 500°C for 2 hours to obtain antibacterial modified titanium dioxide.

[0036] 2) Disperse 3g of the dried antibacterial modified titanium dioxide in step 1) in 50mL toluene and stir for 30 minutes. Then add 24mL of 3-aminopropyltriethoxysilane, stir the reaction mixture and reflux it in a 60℃ nitrogen atmosphere for 8h. After the reaction, use toluene and acetone, centrifuge (3000~6000rpm, 3~7 minutes), vacuum dry and place at 40℃ for 16~30h to obtain amino-modified antibacterial titanium dioxide.

[0037] 3) Disperse 2g of amino-modified antibacterial titanium dioxide in step 2) in 20mL toluene and 2mL triethylamine, stir at 0°C, add 3mL 2-bromopropyl solution, then add bromide and 15mL toluene dropwise within 1h, stir at 0°C for 2h, and finally stir to room temperature overnight. At the end of the reaction, the product is washed with a water / acetone mixture (1 / 1, v / v), centrifuged (3000-7000rpm, 3-8 minutes), vacuum dried at 60°C for 18h, and the reaction obtains bromine-modified antibacterial titanium dioxide.

[0038] 4) Disperse 1g of bromine-modified antibacterial titanium dioxide in step 3) in 10mL of methanol, stir the mixture for 10 to 40 minutes, add 0.5mL of pentamethyldiethylenetriamine and 0.1g of CuBr / 0.1g of CuBr2 to a flask purged with nitrogen. Then add 1mL of methacrylic acid sulfobetaine (SBMA) to the flask and react at 50 to 75°C for 8h by atomic free radical reaction. Finally, the reaction mixture is washed with methanol and acetone, centrifuged (2000 to 6000rpm, 2 to 8 minutes), and vacuum dried at 60°C for 24h to obtain zwitterionic polymer material modified antibacterial titanium dioxide by atom transfer radical polymerization.

[0039] The photo of the modified antibacterial titanium dioxide powder prepared in Example 1 is as follows Figure 1 (a1), the modified antibacterial titanium dioxide powder is slightly yellow in color.

[0040] Example 2, a method for preparing zwitterionic polymer material modified antibacterial titanium dioxide, comprising the following steps:

[0041] 1) comprising preparing 800 mM TiO2 sol by adding 50 mL of tetraisopropyl titanate to 100 mL of isopropanol, and dropping into 1800 mL of deionized water and nitric acid or into 1800 mL of deionized water and nitric acid, while vigorously stirring and fixing the pH at 4. After 24 hours, a transparent TiO2 sol is obtained.

[0042] In order to achieve an Ag content of 3-7 wt.% in the TiO2 nanoparticles, the required amount of AgNO3 1.1 M solution was added to the existing TiO2 sol and stirred for about 30 minutes to allow the Ag to + ions adsorbed onto the TiO2 surface. Then, Ag was reduced by dropwise addition of 400 mL of ascorbic acid (0.2 M). + , until a color change from colorless to brown is observed. In order to increase the specific surface area of ​​the final powder, the gel is dehydrated using the azeotropic dehydration method with benzene. In this process, the colloidal TiO2-Ag nanoparticles are heated to 110°C to obtain a viscous gel. It is then transferred to a double-necked flask containing benzene. The flask is circulated with water and the temperature is raised to 90°C while stirring continuously. When the column is filled with a water-benzene mixture, water is extracted from the outlet. After 24 hours, the yellow solution in the flask is filtered, and finally the prepared powder is calcined in air at 300°C and 500°C for 2 hours to obtain antibacterial modified titanium dioxide.

[0043] 2) Disperse 7g of the dried antibacterial modified titanium dioxide in step 1) in 80mL toluene and stir for 30 minutes. Then add 56mL of 3-aminopropyltriethoxysilane, stir the reaction mixture and reflux it in a nitrogen atmosphere at 80°C for 12h. After the reaction, use toluene and acetone, centrifuge (3000-6000rpm, 3-7 minutes), vacuum dry and place at 50°C for 16-30h to obtain amino-modified antibacterial titanium dioxide.

[0044] 3) Disperse 3g of amino-modified antibacterial titanium dioxide in step 2) in 40mL toluene and 4mL triethylamine, stir at 0°C, add 4mL 2-bromopropyl solution, then add bromide and 20mL toluene dropwise within 1h, stir at 0°C for 2h, and finally stir to room temperature overnight. At the end of the reaction, the obtained product is washed with a water / acetone mixture (1 / 1, v / v), centrifuged (3000-7000rpm, 3-8 minutes), vacuum dried at 60°C for 18h, and the reaction obtains bromine-modified antibacterial titanium dioxide.

[0045] 4) Disperse 2g of bromine-modified antibacterial titanium dioxide in step 3) in 20mL of methanol, stir the mixture for 10 to 40 minutes, add 1mL of pentamethyldiethylenetriamine and 0.2g of CuBr / 0.2g of CuBr2 to a flask purged with nitrogen. Then add 3mL of methacrylic acid sulfobetaine (SBMA) to the flask and react at 50 to 75°C for 10h by atomic free radical reaction. Finally, the reaction mixture is washed with methanol and acetone, centrifuged (2000 to 6000rpm, 2 to 8 minutes), and vacuum dried at 60°C for 24h to obtain zwitterionic polymer material modified antibacterial titanium dioxide by atom transfer radical polymerization.

[0046] Example 3, a method for preparing zwitterionic polymer material modified antibacterial titanium dioxide, comprising the following steps:

[0047] 1) comprising preparing a 500 mM TiO2 sol by adding 40 mL of tetraisopropyl titanate to 70 mL of isopropanol, and dropping the mixture into 1200 mL of deionized water and nitric acid or into 1200 mL of deionized water and hydrochloric acid solution, while vigorously stirring and fixing the pH at 34. After 24 hours, a transparent TiO2 sol is obtained.

[0048] In order to achieve an Ag content of 3-7 wt.% in the TiO2 nanoparticles, the required amount of AgNO3 0.9 M solution was added to the existing TiO2 sol and stirred for about 20 minutes to allow the Ag to + ions adsorbed onto the TiO2 surface. Then, Ag was reduced by dropwise addition of 300 mL of ascorbic acid 0.2 M + , until a color change from colorless to brown is observed. In order to increase the specific surface area of ​​the final powder, the gel is dehydrated using the azeotropic dehydration method with benzene. In this process, the colloidal TiO2-Ag nanoparticles are heated to 110°C to obtain a viscous gel. It is then transferred to a double-necked flask containing benzene. The flask is circulated with water and the temperature is raised to 80°C while stirring continuously. When the column is filled with a water-benzene mixture, water is extracted from the outlet. After 24 hours, the yellow solution in the flask is filtered, and finally the prepared powder is calcined in air at 300°C and 500°C for 2 hours to obtain antibacterial modified titanium dioxide.

[0049] 2) Disperse 8g of the dried antibacterial modified titanium dioxide in step 1) in 80mL toluene and stir for 30 minutes. Then add 64mL of 3-aminopropyltriethoxysilane, stir the reaction mixture and reflux it in a nitrogen atmosphere at 80°C for 12h. After the reaction, use toluene and acetone, centrifuge (3000-6000rpm, 3-7 minutes), vacuum dry and place at 50°C for 16-30h to obtain amino-modified antibacterial titanium dioxide.

[0050] 3) Disperse 6 g of amino-modified antibacterial titanium dioxide in step 2) in 70 mL of toluene and 7 mL of triethylamine, stir at 0°C, add 5 mL of 2-bromopropyl solution, then drop bromide and 23 mL of toluene within 1 hour, stir at 0°C for 2 hours, and finally stir to room temperature overnight. At the end of the reaction, the resulting product is washed with a water / acetone mixture (1 / 1, v / v), centrifuged (3000-7000 rpm, 3-8 minutes), vacuum dried at 60°C for 18 hours, and the reaction obtains bromine-modified antibacterial titanium dioxide.

[0051] 4) Disperse 4g of bromine-modified antibacterial titanium dioxide in step 3) in 40mL of methanol, stir the mixture for 10 to 40 minutes, add 2mL of pentamethyldiethylenetriamine and 0.4g of CuBr / 0.4g of CuBr2 to a flask purged with nitrogen. Then add 6mL of methacrylic acid sulfobetaine (SBMA) to the flask and react at 50 to 75°C for 12h by atomic free radical reaction. Finally, the reaction mixture is washed with methanol and acetone, centrifuged (2000 to 6000rpm, 2 to 8 minutes), and vacuum dried at 60°C for 24h to obtain zwitterionic polymer material modified antibacterial titanium dioxide by atom transfer radical polymerization.

[0052] Examples 4-6 are examples of methods for preparing anti-fouling modified hollow fiber membranes.

[0053] Example 4, a method for preparing an anti-pollution modified hollow fiber membrane, comprising the following steps:

[0054] S1: 13wt% of polyvinylidene fluoride (PVDF), 1wt% of modified materials (modified materials include antibacterial titanium dioxide, polyurethane, sulfonated polysulfone, polymethyl methacrylate), 5wt% of additives (additives include plasticizers, polyvinyl pyrrolidone, polyethylene glycol) and organic solvents (organic solvents include 40wt% N,N-dimethylacetamide and 41wt% ethyl acetate), are mixed and injected into a reactor. After stirring and dissolving at 60°C for 6 hours, polyethylene terephthalate (PET) is used as the lining material. Different additives and solvents are proportioned and adjusted to study the uniformity of the casting liquid and the fusion of nanomaterials and membrane materials.

[0055] S2: After the solution is dissolved, it is transferred to a degassing tank and allowed to stand for degassing at 30°C for 2 hours to obtain a homogeneous casting solution. The degassing casting solution is squeezed from the degassing tank into a metering pump under air pressure and then pumped into a spinneret. The spinneret temperature is controlled at 44°C, and the spinneret temperature is lower than the coagulation bath temperature. If a liner-enhanced hollow fiber membrane is prepared, the treated liner tube is passed through the center of the spinneret. Under the joint action of the braided tube and the metering pump, the casting solution and the braided tube are squeezed out from the spinneret together. The casting solution is evenly coated on the outer surface of the fiber braided tube, and then enters a coagulation bath tank filled with 35°C tap water and a 45°C rinsing tank for phase conversion into a membrane. The membrane fibers after membrane formation are collected by a winding wheel and soaked in pure water for 8 hours, and then soaked in a post-treatment solution for 24 hours to finally obtain a hollow fiber membrane.

[0056] The modified antibacterial titanium dioxide hollow fiber membrane prepared in Example 4 has an inner and outer diameter of 1 mm / 2 mm; water flux per unit membrane area: 1705 LMH (1 bar pressure); maximum transmembrane pressure difference: 0.4 MPa; suspended matter, organic particles (>0.05 μm): 100% removal; microorganisms and pathogens: 99.99% removal, and an antibacterial rate of 99%.

[0057] Figure 1 The photo of the modified antibacterial titanium dioxide hollow fiber membrane prepared in Example 4 is shown in FIG. Figure 1 (a2), the modified antibacterial TiO2 hollow fiber membrane is white.

[0058] Figure 4 This is a test chart of membrane pollution of the modified antibacterial titanium dioxide hollow fiber membrane in Example 4 of the present invention. The first half hour of the cycle test is the relative flux of pure water filtration, the second half hour is the relative flux of bovine serum albumin filtration, the third half hour is replaced by the relative flux of water filtration, and the fourth half hour is the relative flux of bovine serum albumin filtration. From the experimental results, it can be seen that the antibacterial titanium dioxide hollow fiber membrane has the best relative flux of membrane pollution and the smallest membrane pollution, and the membrane pollution of titanium dioxide hollow fiber membrane is better than that of conventional membrane.

[0059] Example 5, a method for preparing an anti-pollution modified hollow fiber membrane, comprising the following steps:

[0060] S1: 10% polyvinylidene fluoride (PVDF), 4% modified materials (modified materials include 2% polyurethane, 1% sulfonated polysulfone, 1% polyvinyl alcohol), 25% additives (additives include 4% saturated fatty acid salts, 2% sorbitan oleate, 10% polyvinyl pyrrolidone, 9% polyethylene glycol) and 61% organic solvents (organic solvents include 20% N,N-dimethylacetamide, 20% triethyl phosphate, 21% dimethyl sulfoxide) are mixed and injected into the reactor. After stirring and dissolving at 70°C for 12 hours, polyethylene terephthalate (PET) is used as the lining material. Different additives and solvents are proportioned and adjusted to study the uniformity of the casting liquid and the fusion of nanomaterials and membrane materials.

[0061] S2: Dissolve the solution in S1 and transfer it to a degassing tank, and let it stand for degassing at 50°C for 5 hours in the degassing tank to obtain a homogeneous casting solution. The degassing casting solution is squeezed from the degassing tank into the metering pump under air pressure and then pumped into the spinneret. The spinneret temperature is controlled at 55°C, and the spinneret temperature is lower than the coagulation bath temperature. If a liner-enhanced hollow fiber membrane is prepared, the treated liner tube is passed through the center of the spinneret. Under the joint action of the braided tube and the metering pump, the casting solution and the braided tube are squeezed out from the spinneret together. The casting solution is evenly coated on the outer surface of the fiber braided tube, and then enters the coagulation bath tank filled with 45°C tap water and the 45°C rinsing tank for phase conversion into a membrane. The membrane fibers after membrane formation are collected by the winding wheel and soaked in pure water for 12 hours, and then soaked in the post-treatment solution for 24 hours to finally obtain a hollow fiber membrane.

[0062] The hollow fiber membrane prepared in Example 5 has inner and outer diameters of 0.9 mm / 2.1 mm; water flux per unit membrane area: 2613 LMH (1 bar pressure); maximum transmembrane pressure difference: 0.5 MPa; suspended matter, organic particles (>0.1 μm): 100% removal; microorganisms and pathogens: 99.99% removal.

[0063] Figure 2 This is a cross-sectional view of the membrane in Example 5 of the present invention. Figure 2 (a1) 900 times magnified electron microscope image, the surface layer of the membrane is relatively thin, and the main body is a sponge-like three-dimensional transparent network structure. Figure 2 (a2) 10k times magnified electron microscope image, the three-dimensional structure of the pores is transparent, which can reduce filtration resistance and enhance membrane performance. Figure 3 The flux of hollow fiber membrane increases with the increase of pressure, and the increasing trend is close to linear.

[0064] Example 6, a method for preparing an anti-pollution modified hollow fiber membrane, comprising the following steps:

[0065] S1: 14% polyvinylidene fluoride (PVDF), 4% modified materials (modified materials include 0.5% titanium dioxide, 1% polyvinyl alcohol, 2.5% polymethyl methacrylate), 25% additives (additives include 1% diethyl phthalate, sorbitan fatty acid ester, 3% plasticizer, 2% Tween 20, 11% polyvinyl pyrrolidone, 8% polyethylene glycol) and 57% organic solvent (organic solvent includes 12% N,N-dimethylacetamide, 35% triethyl phosphate, 10% n-hexanol) are mixed and injected into the reactor. After stirring and dissolving at 60-110°C for 6-24 hours, polyethylene terephthalate (PET) is used as the lining material. Different additives and solvents are proportioned and adjusted to study the uniformity of the casting liquid and the fusion of nanomaterials and membrane materials.

[0066] S2: Dissolve the solution in S1 and transfer it to a degassing tank, and let it stand for degassing at 80°C for 10 hours in the degassing tank to obtain a homogeneous casting solution. The degassing casting solution is squeezed from the degassing tank into a metering pump under air pressure and then pumped into a spinneret. The spinneret temperature is controlled at 70°C, and the spinneret temperature is lower than the coagulation bath temperature. If a liner-enhanced hollow fiber membrane is prepared, the treated liner tube is passed through the center of the spinneret. Under the joint action of the braided tube and the metering pump, the casting solution and the braided tube are squeezed out from the spinneret together. The casting solution is evenly coated on the outer surface of the fiber braided tube, and then enters a coagulation bath containing 83°C tap water and a 35-75°C rinsing tank for phase conversion into a membrane. The membrane fibers after membrane formation are collected by a winding wheel and soaked in pure water for 48 hours, and then soaked in a post-treatment solution for 24 hours to finally obtain a hollow fiber membrane.

[0067] The hollow fiber membrane prepared in Example 6 has an inner and outer diameter of 0.8 mm / 2.1 mm; water flux per unit membrane area: 1913 LMH (1 bar pressure); maximum transmembrane pressure difference: 0.5 MPa; suspended matter, organic particles (>0.1 μm): 100% removal; microorganisms, pathogens: 99.9% removal.

[0068] Figure 5 This is a diagram of the iron block hanging of the hollow fiber membrane in Example 6 of the present invention. The results show that the hollow fiber membrane has strong tensile strength and can be kept from breaking during high-intensity operation and pulling.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a pollution-resistant modified hollow fiber membrane, characterized in that: The following steps are involved: S1: 8% to 30% of polyvinylidene fluoride PVDF or polysulfone or polyethersulfone, 0.1% to 15% of modified material, 0.1% to 30% of additives and 25% to 88.9% of organic solvent are mixed and injected into a reaction kettle, and stirred and dissolved at 60 to 110° C. for 6 to 24 hours; S2: Dissolve the solution in S1 and transfer it to a degassing tank, and place it in the degassing tank at 30-80°C for 2-10 hours to obtain a homogeneous casting solution. Squeeze the degassing solution from the degassing tank into a metering pump at 0.5-3 bar and then pump it into a spinneret. The temperature of the spinneret is controlled at 44-70°C, which is lower than the temperature of the coagulation bath. Then, the membrane is immersed in a coagulation bath tank filled with tap water at 25-83°C and a rinsing tank at 35-75°C in turn for phase transformation into a membrane. The membrane is immersed in the coagulation bath tank and the rinsing tank for 1-600 seconds respectively. The membrane fibers after membrane formation are collected through a winding wheel and immersed in pure water for 8-48 hours. After being immersed in a post-treatment solution for 24 hours, an anti-pollution modified hollow fiber membrane is obtained.

2. The method for preparing a pollution-resistant modified hollow fiber membrane according to claim 1, characterized in that: After the degassed casting liquid is injected into the spinneret and before it is immersed in the coagulation bath, the following steps are added to finally obtain the lining-enhanced anti-pollution modified hollow fiber membrane: the treated lining tube is passed through the center of the spinneret, and under the joint action of the braided tube and the metering pump, the degassed casting liquid and the fiber braid are squeezed out of the spinneret together, and the degassed casting liquid is evenly coated on the outer surface of the fiber braided tube.

3. The method for preparing a pollution-resistant modified hollow fiber membrane according to claim 1, characterized in that: The modified material in S2 is one or more of titanium dioxide, other metals or metal oxides, zwitterionic polymer modified antibacterial titanium dioxide, polyurethane, sulfonated polysulfone, polymethyl methacrylate, amino polysulfone, polyvinyl alcohol and chitosan.

4. The method for preparing a pollution-resistant modified hollow fiber membrane according to claim 1, characterized in that: The additives in S2 include one or more of plasticizer, dibutyl phthalate, silicone polymer, glycerol, diethyl phthalate, polysorbate 80, saturated fatty acids, sorbitan fatty acid esters, saturated fatty acid salts, sodium dodecylbenzene sulfonate, sodium glycocholate, sodium linear alkylbenzene sulfonate, sorbitan oleate, Tween 20, Span 85, polyethylene glycol, glutaraldehyde, epichlorohydrin and polyvinyl pyrrolidone.

5. The method for preparing a pollution-resistant modified hollow fiber membrane according to claim 1, characterized in that: The organic solvent in S2 is one or more of propylene glycol, glacial acetic acid, phytic acid, isopropanol, n-hexane, n-heptane, n-hexanol, acetone, methanol, triethyl phosphate, N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide and ethyl acetate.

6. The method for preparing a pollution-resistant modified hollow fiber membrane according to claim 3, characterized in that: The preparation method of the zwitterionic polymer material modified antibacterial titanium dioxide is as follows: 1) Add 20 to 50 parts of tetraisopropyl titanate to 40 to 110 parts of isopropanol, and then dropwise add the mixture to 800 to 2000 parts of deionized water and nitric acid, or deionized water and hydrochloric acid solution, while stirring vigorously and fixing the pH at 1 to 4. After 24 hours, a transparent TiO2 sol is obtained. Add the required amount of AgNO3 0.8-1.1 parts solution to the aforementioned TiO2 sol and stir for 10-40 minutes to allow Ag to + ions adsorbed onto the TiO2 surface; then, Ag was reduced by dropwise addition of 0.2 parts of ascorbic acid (200-400 mL). + , until a color change from colorless to brown is observed to obtain colloidal TiO2-Ag nanoparticles; The colloidal TiO2-Ag nanoparticles were heated to 110°C to obtain a viscous gel, which was then transferred to a double-necked flask containing benzene. The flask was circulated with water and the temperature was raised to 70-100°C while stirring continuously. When the column was filled with a water-benzene mixture, water was extracted from the outlet. After 24 hours, the yellow solution in the flask was filtered, and finally the prepared powder was calcined in air at 300°C and 500°C for 2 hours to obtain antibacterial modified titanium dioxide; 2) Dispersing 3 to 20 parts of the dried antibacterial modified titanium dioxide in step 1) in 50 to 500 parts of toluene and stirring for 30 minutes, then adding 20 to 100 parts of 3-aminopropyltriethoxysilane, stirring the reaction mixture, and refluxing in a nitrogen atmosphere at 60 to 150° C. for 8 to 20 hours. After the reaction is completed, using toluene and acetone, centrifuging, vacuum drying and placing at 40 to 70° C. for 16 to 30 hours to obtain amino-modified antibacterial titanium dioxide; 3) Disperse 1 to 15 parts of the amino-modified antibacterial titanium dioxide in step 2) in 20 to 150 parts of toluene and 2 to 9 parts of triethylamine, stir at 0°C, add 3 to 6 parts of 2-bromopropyl solution, then add the bromide and 15 to 25 parts of toluene dropwise within 1 hour, stir at 0°C for 2 to 5 hours, and finally stir at room temperature overnight. At the end of the reaction, the product is washed and centrifuged with a water / acetone mixture, vacuum dried and placed at 60°C for 18 to 30 hours to obtain bromine-modified antibacterial titanium dioxide. 4) Disperse 1 to 10 parts of bromine-modified antibacterial titanium dioxide in step 3) in 10 to 200 parts of methanol, stir the mixture for 10 to 40 minutes, add 0.5 to 4 parts of pentamethyldiethylenetriamine and 0.1 to 5 parts of CuBr / 0.1 to 5 parts of CuBr2 to a flask purged with nitrogen. Then add 1 to 15 parts of methacrylic acid sulfobetaine (SBMA) to the flask, and react at 50 to 75°C for 8 to 15 hours through atomic free radical reaction. Finally, the reaction mixture is washed with methanol and acetone, centrifuged (2000 to 6000 rpm, 2 to 8 minutes), and vacuum dried at 60°C for 24 hours to obtain zwitterionic polymer material modified antibacterial titanium dioxide through atom transfer radical polymerization.

7. A pollution-resistant modified hollow fiber membrane, characterized in that: The method is prepared by any one of claims 1 to 6.

8. An application of a hollow fiber membrane, characterized in that: The hollow fiber membrane is prepared as claimed in any one of claims 1 to 6, and is used in wastewater treatment, pollution prevention and control, comprehensive utilization of water resources, food processing and pharmaceutical purification.

Citation Information

Patent Citations

  • Surface modification method for polyvinylidene fluoride (PVDF) film or polyvinyl chloride (PVC) film

    CN102558595A

  • Polyvinylidene-fluoride hollow fibre membrane and preparation method thereof

    CN102836645A

  • Hollow polyethersulfone fiber ultrafiltration membrane capable of resisting biological pollution and preparation method of membrane

    CN103977717A

  • PVDF membrane with antifouling property and preparation method of PVDF membrane with antifouling property

    CN104437122A

  • PES ultra-filtration film loaded with Ag-TiO2 and preparation method and application of PES ultra-filtration film

    CN107376658A

Cited By

  • Vitamin B12 preparation composition and preparation method thereof

    CN119700662A

  • Preparation method of mussel mucin

    CN120519544A

  • A method for preparing a mussel adhesive protein

    CN120519544B